DINAMIKA PENERAPAN AKAD SYARIAH DALAM PRODUK KEUANGAN DI BANK SYARIAH - Jaenudin Jaenudin (Asy-Syari'ah, 2020)
Abstract: Sociologically, the existence of Islamic banks in Indonesia had developed since the early 1990 through a long time of workshops and bureaucratic processes until Bank Muamalat Indonesia was established as the first Islamic bank in Indonesia. The existence of Bank Muamalat Indonesia, as the first Islamic bank, has a mission to present an Islamic banking institution that is free from the interest system by replacing its operational system through Islamic principles. Normatively, the profit sharing concept used to an operational system for Islamic banks in Indonesia which has been regulated in Article 1 Number 12 of the Law of Banking Number 7 of 1992, then the dual banking system in Article 9 of the Law of Banking Number 10 of 1998, and the latest. is the application of Islamic principles in the Law of Islamic Bank Number 21 of 2008 through using six patterns: first, the deposit through the wadi'ah contract; second, borrowing through qard and qardh al-hasan contracts; third, the profit sharing scheme through mudharabah and syirkah contracts; fourth, buying and selling through murabahah, salam, and istishna' contracts; fifth, the rental scheme through ijarah and ijarah muntahiya bi al-tamlik contracts; and sixth, the services through wakalah, kafalah, hiwalah, ujr, sharf, and rahn contracts. The result of this study shows that the changes of Islamic banking regulations have implications to the dynamics of Islamic contract implementation in Islamic banking financial products in Indonesia.Abstrak: Secara sosiologis eksistensi bank syariah di Indonesia sudah berkembang sejak awal tahun 1990-an melalui serangkaian proses panjang lokakarya dan birokrasi sehingga berdiri Bank Muamalat Indonesia sebagai bank syariah pertama di Indonesia. Eksistensi Bank Muamalat Indonesia sebagai bank syariah memiliki misi untuk menghadirkan lembaga perbankan syariah yang bebas dari sistem bunga dengan mengganti sistem opersionalnya dengan prinsip-prinsip Islam. Penggunaan konsep bagi hasil sebagai sistem operasional bank syariah di Indonesia secara normatif telah diatur dalam Undang-Undang Nomor 7 Tahun 1992 tentang Perbankan pada Pasal 1 angka 12, kemudian dual banking system dalam Pasal 9 Undang-Undang Nomor 10 Tahun 1998 dan yang terkahir adalah penerapan prinsip syariah dalam Undang-Undang Nomor 21 Tahun 2008 dengan menggunakan enam pola: pertama, pola titipan melalui akad wadi’ah; kedua, pola pinjaman, melalui akad qard dan qardh al-hasan; ketiga, pola bagi hasil melalui akad mudharabah dan syirkah; keempat, pola jual beli melalui akad murabahah, salam, dan istishna’; kelima, pola sewa melalui akad ijarah dan ijarah muntahiya bi al-tamlik; keenam, pola jasa melalui akad wakalah, kafalah, hiwalah, ujr, sharf, dan rahn. Hasil penelitian ini menunjukan bahwa perubahan regulasi perbankan syariah telah berimplikasi terhadap dinamika penerapan akad syariah dalam produk keuangan bank syariah di Indonesia.